Combining ability analysis and correlation studies for yield and mineral nutrients in ridge gourd (Luffa acutangula) - SINGH, JOGENDRA; MUNSHI, A D; SUREJA, A K; SRIVASTAVA, ARPITA; GUPTA, NAKUL; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2019)
The current study was carried out to determine combining ability and association of yield and yield components in 7 × 7 half-diallel crosses of ridge gourd (Luffa acutangula Roxb.) at ICAR-IARI, New Delhi in the year 2016. Twenty one F1 hybrids along with seven parental lines were grown in randomized block design in three replications. The mean square due to GCA and SCA were highly significant for all the characters indicating the importance of additive and non-additive genetic components for the traits under study. Further, SCA variance was more than GCA variance for all the characters which suggested the importance of non-additive variance for the improvement of these characters. The parental lines Pusa Nutan, DRG-7, DRG-71 and Pusa Nasdar were good combiners for most characters under study including yield and mineral nutrients. The hybrid combination of Pusa Nutan × Arka Sujat, Pusa Nasdar × Co-1 and Pusa Nasdar × Swarna Uphar were found to be most promising combinations for earliness, yield, mineral content and other economic traits of interest. Significant positive correlations were observed between yield and fruit length, average fruit weight and number of fruits per plant. The results indicated the importance of heterosis breeding for effective utilization of non-additive genetic variance in ridge gourd.